Keberlanjutan Pariwisata Gastronomi di Indonesia: Konteks Teoritis - Nilam Sukma; Jhon Irvan F Hutahaean; Asep Parantika (Peneliti.net, 2023)
Being part of the hospitality and tourism industry, gastronomic tourism can be called one of the elements for tourists to assimilate with the culture and lifestyle of a country. With the aim of embodying different traditional values ​​associated with the countries they visit. The role of gastronomic tourism has contributed to the growth of gastronomic experiences among tourists, especially in the quality and sustainability of local culinary products, and the landscape of traditions, culture and lifestyle. Seeing the rapid growth of gastronomic tourism in Indonesia, it is important for hoteliers and tourism actors to promote and broaden tourists' insights about local culture and cuisine. It aims to find out about the sustainability of gastronomic tourism in Indonesia. By reviewing the literature related to sustainability in the hospitality and tourism sector, this study highlights the correlation between Indonesia's gastronomic heritage using 3 components of sustainable tourism namely economic, social and environmental sustainability. Research will be better if it is observed in reality as well as non-reality to reveal the linkages between the three primary components in maintaining the gastronomic tourism landscape in Indonesia